REDESIGNING A COMPETENCY-BASED SYLLABUS OF ENGLISH FOR INFORMATION TECHNOLOGY: A CASE STUDY AT UNISBANK - Sugeng Purwanto; Wienny Ardriyati (Universitas Stikubank (UNISBANK) Semarang, 2013)
This study isabout redesigning the competency-based syllabus of English for InformationTechnology at Facultyof Information Technology UNISBANK Semarang of which the graduates are supposedto be able to speak English in accordance with the scientificfield. This is an exploratory descriptive qualitativeresearch because it will address issues defined by exploration and describe thesymptoms to redesign the English syllabus for InformationTechnique Faculty Program tobe competency-based syllabus. The finding of redesigning syllabus for Informatics Technique Program is acompetency-basedcurriculum and giveweight SKS, especially Englishinto at least 4credits to accommodate theinterests of students who want aspecial competence in English informatics techniques. The competency standards are successfully identified is that, aftercompleting the course in English,students can be experts in all fourlanguage skills. Competency standardswill be further decomposedinto basic competenciesfor each learning unit.KEY WORDS: syllabus, competency, SWOT analysis, SKS